Peningkatan Aktivitas Dan Hasil Belajar Mata Diklat Produktif Pemasaran Dengan Menggunakan Metode Inkuiri - Tri Nurwati (Jurnal Ekonomi dan Pendidikan, 2010)
The objectives of this research are to describe the inquiry method in order to minimize students bored in teaching learning history lesson and to find out whether inquiry method can improve students activity in teaching learning and also to know whether inquiry method are able to improve students achievement in learning the history lesson.This research is a classroom action research. The writer conducted two cyclists. The cyclists consist of planning, acting, observing and reflecting. At the last cyclist, the researcher did reflection and evaluation to know the students ability and to choose what the next strategy in teaching learning by using inquiry method.The result of the tests show that the students achievement in their activity is 50,72 % in pra cyclist, 63,88 % in cyclist one, 80,55 % in cyclist two, and 94,44% in cyclist three. The students achievement has improved from 70,19 in pra cyclist, 73,02 in cyclist one, 76,52 in cyclist two, and 80,11% in cyclist three. While the grade of students classical graduate have improved that is 55,77% in pra cyclist, 66,67% in cyclist one, 75,00% in cyclist two, and 97,22% in cyclist three. Afterr compring the result of the research, the writer conclude that by using inquiry method in teaching learning the history subject can improve the students activity and achievement. By using inquiry method is recommended to be able to apply to other material in order toimprove the students activity and achievement.